Antifungal Action of Metallic Nanoparticles Against Fungicide-Resistant Pathogens Causing Main Postharvest Lemon Diseases - Baigorria, Carina Giselle (2024)
Postharvest fungal diseases are the main cause of economic losses in lemon production. The continued use of synthetic fungicides to control the diseases favors the emergence of resistant strains, which encourages the search for alternatives. The aim of this study was to assess the efficacy of metallic nanoparticles (NPs) as antifungal agents against local isolates of Penicillium digitatum and Penicillium italicum, each of them in a fungicide-sensitive and -resistant version, and a Geotrichum citri-aurantii isolate. NPs of ZnO, CuO, and Ag were synthesized and characterized by spectroscopy and microscopy, presenting average sizes < 25 nm and spherical shapes. ZnO-NPs did not present antifungal activity at the assayed conditions, while the minimum fungicidal concentrations (MFCs) were 1000 and 10 µg mL−1 for CuO-NPs and Ag-NPs, respectively. The NPs’ antimicrobial action included conidial membrane permeability and strong intracellular disorganization. Moreover, the Ag-NPs reduced green mold incidence on inoculated lemons when applied to the fruit. Taken together, Ag-NPs were effective in inhibiting both fungicide-sensitive and -resistant isolates of the main lemon postharvest pathogens, suggesting their potential use as an alternative approach.